Surgical Procedure for a Rare Case of Skull Bone Cysts: A Case Report - Rafiqi, Ahmad; Hutagalung, Tommy Rizky; Farhan, Luthfy; Diandra, Muhammad Aga Firza; Ananda, Sigit (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2023)
Introduction: Bone cysts are inclusive of but not limited to the unicameral bone cyst (UBC) and aneurysmal bone cyst (ABC). UBC have a predilection for males (3:1). UBC make up 3% of primary bone lesions. Most UBCs are found in long bones, most common sites are proximal humerus and femurs, rarely found in flat bones (Skull). Cases of UBC observed following trauma are thought to occur due to intraosseous bleeding when bone organization or repair mechanisms fail. Case Report: Twenty-one-year-old male complained of headache, a history of traumatic brain injury. Motoric examinations show diminished motor function on the left side. CT Scan shows an expansile sclerotic lytic lesion on the right parietal bone. We diagnosed this case with a suggested Bone Cyst on the right parietal, and craniotomy tumor removal with a direct approach was performed. Thickened dura mater was identified, cleansed using NaCL and povidone-iodine, and drilled using a high-speed drill until flattened. The yellowish-colored bony lesion was discovered to contain a semi-translucent substance, the lesion was found to be a unicameral bone cyst. Discussion: UBCs are generally asymptomatic, and usually appear as lesions with lucent characteristics and small zones of transition. As a benign bone tumor, treatments are not required unless the lesion is large and symptomatic, due to the patient's symptomatic condition, craniotomy tumor removal was performed. Conclusion:UBC is a rare condition, that’s scarcely located in the skull. Post-operatively, the patient shows normal motor function and no complaint of pain. Craniectomy tumor removal and flattening of the dura mater using a high-speed drill is sufficient in treating this rare disease.